Possibilities of Using Tram Windscreen Impact Tests in Analysis of Human-Machine Accidents - Bittner, Vaclav; Jezdik, Roman; Kubovy, Petr; Lopot, Frantisek; Stocek, Ondrej; Havlicek, Martin; Svoboda, Martin; Jelen, Karel (Manufacturing Technology Journal, 2019)
The main aim of this article is to show the possibilities of using tram windscreen impact tests in the analysis of human-machine accidents. Empirical experience shows that these accidents especially affect the head, which is at the same time one of the most vulnerable parts of the human body. Windscreen safety testing follows ECE standards and, inter alia, involves collisions with a headform. With regards to numerical simulations, however, it is essential to be able to determine the material characteristics of windscreens. Here it seems to be advantageous in terms of validity, reliability and the economic cost of using collisions with a rigid body where only the glass absorbs all of the kinetic collision energy. The outcome of these tests is a waveform of the cont act force's magnitude as a function of deformation in the direction the force acts. Along with the time course of acceleration of the bumper and its kinetic energy on impact, this information can serve as boundary conditions to verify mathematical models.
Keywords: impact tests; human-machine accidents; tram; windscreen